Critical thinking - Moore, Brooke Noel.; Parker, Richard (Richard B.). (Boston, MA McGraw-Hill, 2009)
Critical thinking basics -- Clear thinking, critical thinking, and clear writing -- Credibility -- Persuasion through rhetoric : common devices and techniques -- More rhetorical devices : psychological and related fallacies -- More fallacies -- The anatomy and varieties of arguments -- Deductive arguments I : categorical logic -- Deductive arguments II : truth-functional logic -- Inductive arguments -- Causal arguments -- Moral, legal, and aesthetic reasoning.
Includes bibliographical references and index.
Keywords: Critical thinking; Logic học